VERTICAL INTEGRATION IN THE APPLICATION OF PESTICIDES IN BRAZIL: A GOVERNANCE PROPOSAL FOR REDUCING SANITARY AND ENVIRONMENTAL RISKS - dos Santos, Jeronimo Alves (Seven Editora, 2026)
This article analyzes the public health and environmental risks associated with pesticide use in Brazil and discusses how governance arrangements can influence the quality of on-farm application. Through a comparative literature review of three models (direct sales, outsourcing, and downstream vertical integration), the study synthesizes evidence on recurrent shortcomings in use (dosage, personal protective equipment, disposal, and resistance management), particularly in settings with limited technical assistance. It proposes an industry-linked technical application service model incorporating mechanisms for traceability, operational standardization, and accountability. The article concludes that a partial shift from a sales-based model to a service-based model can reduce risks, provided it is accompanied by regulation, independent auditing, and safeguards for smallholders.